(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Hemidesmusindicus (L) is avaluable source of severaleffective principles of therapeutic value. It is an important medicinal herb used in the traditional system of Ayurvdicmedicine in India for drug development. The aim of our present study deals with the development of invitro propagation of callus from the explant of Hemidesmus indicus, production of biomass culture by the cell suspension culture. Leaf explants were cultured on MS medium supplemented with different concentrations of plant growth regulators such as BA (2 mg/l), 2, 4 D (1 and 2 mg/l), NAA + Kinetin (2 + 1 mg/l) and NAA + Kinetin (1 + 2mg/l) respectively. The established calli were transferred into a different carbohydrates suspension cell cultures was produced the secondary metabolites. Results showed the goodcallus establishment was observed by BA at 2 mg/l within 7 – 9 days of incubation than other supplements and the great biomass yield of secondary metabolites was produced by the treatment of G5, M3 and S1based on fresh and dry weight.